2018
DOI: 10.1016/j.hpb.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of central pancreatectomy in pancreatic surgery: a systematic review and meta-analysis

Abstract: CP maintains pancreatic endocrine and exocrine function better than DP and PD, but is associated with a higher PF rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 51 publications
2
53
2
4
Order By: Relevance
“…Since then, an increasing number of cases have been reported. Some systematic reviews and meta-analyses [9][10][11] showed that CP could decrease the risk of exocrine failure and impairment of endocrine function than DP, although it was associated with a slightly higher postoperative morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, an increasing number of cases have been reported. Some systematic reviews and meta-analyses [9][10][11] showed that CP could decrease the risk of exocrine failure and impairment of endocrine function than DP, although it was associated with a slightly higher postoperative morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Though CP has a higher risk of pancreatic fistula, it maintains pancreatic endocrine and exocrine function better than distal pancreatectomy and pancreaticoduodenectomy. Pancreas preserved operation provides better long-term outcomes 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1982, Dagradi and Serio first reported CP with reconstruction of pancreas by oversewing the cephalic stump and performing an end-to-end pancreatojejunostomy for the distal pancreatic stump 2 . This procedure is considered safe and optimizes the quality of patients' life. Up to now, Dagradi and Serio' method is the conventional procedure in open and minimally invasive surgery [4][5][6] .But it has a higher risk of pancreatic fistula 1 . Various studies indicate that the use of pancreatojejunostomy may lead the high risk of pancreatic fistula [7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, it was believed that pancreatectomy had high mortality and morbidity rates; however, recent clinical analyses of large sample sets have revealed that a pancreatectomy has low mortality rates and acceptable morbidity rates, and the operation for pancreas metastases is safe [ 17 , 21 , 27 ]. Xiao et al [ 28 ] reported that medial pancreatectomy maintains pancreatic endocrine and exocrine function better than other standardized pancreatic resections, which is suitable for benign or low grade malignant lesions. In previous literatures, the perioperative mortality rate has been reported as being 1–3% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%